2014
DOI: 10.1128/aac.02735-13
|View full text |Cite
|
Sign up to set email alerts
|

His224 Alters the R2 Drug Binding Site and Phe218 Influences the Catalytic Efficiency of the Metallo-β-Lactamase VIM-7

Abstract: b Metallo-␤-lactamases (MBLs) are the causative mechanism for resistance to ␤-lactams, including carbapenems, in many Gramnegative pathogenic bacteria. One important family of MBLs is the Verona integron-encoded MBLs (VIM). In this study, the importance of residues Asp120, Phe218, and His224 in the most divergent VIM variant, VIM-7, was investigated to better understand the roles of these residues in VIM enzymes through mutations, enzyme kinetics, crystal structures, thermostability, and docking experiments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
(97 reference statements)
1
26
0
Order By: Relevance
“…In addition there are two stabilizing hydrogen bonds in VIM‐2 involving Tyr224 . We later confirmed this through structural and kinetic studies of a His224Tyr mutation of VIM‐7 where we could show that the mutant was more active against positively charged cephalosporins compared to the wild‐type VIM‐7 . In a VIM‐2 thiol based inhibitor complex it was found that both Arg228 and Asn233 are important for inhibitor binding and recognition .…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition there are two stabilizing hydrogen bonds in VIM‐2 involving Tyr224 . We later confirmed this through structural and kinetic studies of a His224Tyr mutation of VIM‐7 where we could show that the mutant was more active against positively charged cephalosporins compared to the wild‐type VIM‐7 . In a VIM‐2 thiol based inhibitor complex it was found that both Arg228 and Asn233 are important for inhibitor binding and recognition .…”
Section: Introductionmentioning
confidence: 53%
“…Compared to the other VIM variants, the overall trend was that VIM‐26 and periplasmic purified VIM‐7 were more efficient penicillinases than VIM‐1 and VIM‐2 (Table ). In contrast both VIM‐1 (all cephalosporins) and to a certain degree VIM‐2 (ceftazidime and cefoxitin) were more efficient cephalosporinases than VIM‐26 and VIM‐7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tyrosine at 224 position in VIM-2 contributes to enhanced binding of positively charged substrates, such as ceftazidime and cefepime, compared to the arginine and lysine present at this position in TMB-1, NDM-1, and GIM-1, as shown for the VIM-7 H224Y mutant (36).…”
Section: Figmentioning
confidence: 99%
“…Residue 228 has not been shown to be involved in the binding of penicillin substrates with small R2 groups; however, the residue seems to affect neighboring residues in the active site, including the L3 loop, which again affects the binding of penicillin substrates. Residue 228 is located adjacent to the active-site Zn2 in the so-called R2 binding site (36) and is a part of the MBL L3 loop. Substitutions at position 228 have been shown to be tolerated for different substrates (37) but have also been found to affect the substrate specificity of, e.g., GIM-1 (25).…”
mentioning
confidence: 99%